Penguatan Kelembagaan dan Peningkatan Kualitas SDM dalam Pengelolaan Sampah - Muhammad Eko Atmojo; Nur Fitri Mutmainah; Vindhi Putri Pratiwi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
The waste problem is still a severe problem that must be addressed immediately. The problem is related to the final disposal site (TPA) and how and technically waste management and the lifestyle of the people themselves so that it is not only the role of the government in dealing with the waste problem but also the role of the community. Therefore, this community service aims to strengthen institutions and improve the quality of human resources in waste management. In the village of Ngestiharjo, Bantul Regency already has a partner waste bank, but the community has not engaged in waste bank management. Through this community service, the community is given socialization and motivation as education and encourages the community to move back to the existing waste bank. Not only that but the community was also given training in waste management. As well as for institutional improvement, the community is equipped with roles and tasks.